2018
DOI: 10.2166/wh.2018.393
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine inactivation of coxsackievirus B5 in recycled water destined for non-potable reuse

Abstract: Currently guidelines for disinfection of water with free chlorine, while primarily developed for potable water, are often used for virus disinfection of nitrified recycled water of >1 NTU (Nephelometric Turbidity Unit). More information is needed on the disinfection efficacy of free chlorine for viruses in waters of varying turbidity and pH due to significant reuse of treated wastewater of varying quality. In this study, disinfection efficacy in nitrified/denitrified activated sludge treated wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Wang et al (2005b) reported that SARS-CoV can be inactivated completely by 20 mg/L chlorine in 1 min. They observed that Chlorine dioxide was less effective for the inactivation of SARS-CoV as compared with free chlorine, similar results have been reported for other viruses (Young et al, 2020b;Wati et al, 2019;Cromeans et al, 2019;Lim et al, 2010). Chlorine has been reported to inactivate viruses through the cleavage of the capsid protein backbone of viruses, therefore inhibiting viral genome injection into host cells Page et al, 2010).…”
Section: Removal Of Coronavirus During Wastewater Treatmentsupporting
confidence: 61%
“…Wang et al (2005b) reported that SARS-CoV can be inactivated completely by 20 mg/L chlorine in 1 min. They observed that Chlorine dioxide was less effective for the inactivation of SARS-CoV as compared with free chlorine, similar results have been reported for other viruses (Young et al, 2020b;Wati et al, 2019;Cromeans et al, 2019;Lim et al, 2010). Chlorine has been reported to inactivate viruses through the cleavage of the capsid protein backbone of viruses, therefore inhibiting viral genome injection into host cells Page et al, 2010).…”
Section: Removal Of Coronavirus During Wastewater Treatmentsupporting
confidence: 61%
“…It is one of the most frequently detected genotypes in clinical and wastewater surveillance. Furthermore, the laboratory strain of CVB5, the Faulkner strain, exhibited lower susceptibility to free chlorine than other genotypes of enteroviruses, adenoviruses, and murine norovirus, and thus has been recognized as the most free chlorine resistant among enteric viruses. In fact, infective CVB5 has been detected from disinfected drinking water. , These studies made researchers consider incorporating the data of the required CT values of CVB5 into the USEPA Guidance manuals as the worst-case scenario in drinking water and wastewater reclamation treatment. The inactivation of CVB5 during drinking water treatment should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 These models do not include the effects of water quality, which impacts virus LRVs. 55,56 In this study, we established predictive inactivation models in chloramine disinfection by regularized regression analyses, in which the water quality parameters were used as explanatory variables. Our established models estimated LRVs by inputting several water quality and operational parameters, and were able to avoid over-and/or under-estimation of the LRV by combining hierarchical Bayesian or using error distributions, which can be applied for each WWTP treating different water qualities.…”
Section: Discussionmentioning
confidence: 99%